Early alert from the microbiology laboratory improves the outcome of elderly patients with Enterococcus spp. bloodstream infection: Results from a multicentre prospective study. (September 2019) - Falcone, M.; Tiseo, G.; Dentali, F.; Foglia, E.; Campanini, M.; Menichetti, F.; Mazzone, A.; ,
Highlights: Elderly patients with Enterococcal bacteremia had high mortality risk. Polymicrobial infection, age and SOFA score are predictors of poor outcome. Improving communication between microbiology and clinicians is associated with better outcome. Abstract: Objectives: This study describes the clinical features and outcomes of patients with bloodstream infection (BSI) due to Enterococcus spp. and identified factors predictive of mortality. Methods: This analysis is part of a prospective multicentre observational study of consecutive hospitalised patients with BSI conducted from March 2012 to December 2012 in 31 internal medicine wards in Italy. Patients with enterococcal BSI were selected from the entire cohort. Patient characteristics, therapeutic interventions and outcome were reviewed. Cox regression analysis was performed to identify factors associated with in-hospital mortality. Hazard ratios (HRs) and 95% interval confidences (CIs) were calculated. Results: Among 533 patients with BSI, 41 (7.7%) had BSI by Enterococcus spp. (28 Enterococcus faecalis, 4 Enterococcus faecium and 3 each of Enterococcus avium, Enterococcus casseliflavus and Enterococcus gallinarum ). Six BSIs (14.6%) were polymicrobial. Median (IQR) patient age was 73 (66–85.5) years. In-hospital mortality was 24.4%. Polymicrobial infection (HR = 9.100, 95% CI 1.295–63.949; P = 0.026), age (HR = 1.261, 95% CI 1.029–1.546; P = 0.025) and SOFA score (HR = 1.244, 95% CI 1.051–1.474; P = 0.011) were risk factors for in-hospital mortality. Conversely, receiving an alert from the microbiology laboratory before obtaining final antimicrobial susceptibility results was associated with survival (HR = 0.073, 95% CI 0.007–0.805; P = 0.033). Conclusion: BSI due to Enterococcus spp. in elderly patients is associated with high mortality. Polymicrobial infection, age and SOFA score are factors associated with poor outcome. Conversely, early alert from the microbiology laboratory improves patient survival.